Culicídeos vetores em uma unidade de conservação da caatinga na região do seridó no Rio Grande do Norte aspectos da transmissão de doenças - Fernandes, Gláucia de Oliveira (2011)
The scarcity of occurrence records of culicid species, transmitting insects of etiologic agents for arboviruses, protozoan diseases and philarioses, and lack of information about their interactions with the forest environment make the Caatinga one of the most unknown biomes in Brazil. The aim of this study was to identify culicid species in a conservation unit located in a preserved area of the Caatinga and the possible associations with local abiotic factors, as well as characterize the natural and artificial ecotopes present in the Caatinga of Rio Grande do Norte state. The Ecological Station of Serido (ESEC-Seridó) is a Caatinga Conservation Unit located in a rural area of Rio Grande do Norte. The hot and dry climate of the Caatinga, along with a short rainy season, favor the adaptation and resistance of plants, resulting in completely distinct landscapes over the course of the year. The study took place over the course of one year, with monthly collections between 10h-12h, 14h-16h and 18h-20h. Adult mosquitoes were collected in a forest area using a manual suction trap with human bait as attractant at the three times and a Shannon trap for night collections. During the rainy season ovitraps were randomly distributed at different sites. The different capture sites were observed and photographed. Immature and adult insects captured were taken to the laboratory for identification. Of the 5081 insects collected in human-bait and Shannon traps, 75% were Mansonia wilsoni. In addition, Aedeomyia, Aedes, Anopheles, Coquillettidia, Culex, Haemagogus, Mansonia and Psorophora were identified. Of the 92 Haemagogus eggs found, 71 were collected on the banks of a reservoir. Mosquito larvae were found and photographed in an artificial breeding site of a neighboring rural area. Humidity had the greatest influence on culicid density in the Caatinga. Rain was important in the appearance of Haemagogus, Anopheles, Aedes and Psorophora. Temperature had a negative influence on Anopheles triannulatus. The occurence of important vector species of diseases in a little known preserved area of the Caatinga as well as environmental and sociocultural questions are factors that favor the emergence of transmitting insects, making these areas potential subject to the resurgence of diseases